INFORMATION SUPPORT IN HOUSING FUND MANAGEMENT - Inoyatova Durdona Shoxaydarovna (Web of Journals Publishing, 2025)
This article explores the role of information provision in the housing stock management system, examines existing information flows, and discusses ways to enhance their effectiveness.
Keywords: Housing stock, digitalization, technical and economic passports for multi-apartment buildings, infrastructure, information database.